2014
DOI: 10.1080/14786419.2014.924934
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and antimicrobial properties of the essential oil and ethanol extract from the stem of Aglaia odorata Lour.

Abstract: The stem-derived essential oil of Aglaia odorata Lour. was obtained by hydrodistillation using a Clevenger-type system. Gas chromatography-mass spectrometry analysis of the oil revealed the identification of 39 compounds, representing 76.4% of the oil; germacrene D (20.3%), α-humulene (17.1%), α-himachalene (12.7%) and β-caryophyllene (10.2%) were the major components. Ar-turmerone (1) and eichlerialactone (2) were isolated from the stem oil and ethanolic stem extract of this plant species, respectively. Antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In our study, this oil demonstrated only poor antibacterial and antifungal activity (Table S1). On the contrary, low percentages of borneol and α-pinene in Ampelopsis megalophylla as reported by Xie et al (2014) and caryophyllene (Joycharat et al 2014) show high microbiological activity. TTO which exhibited MIC values of 3.12 mg/ml.…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 65%
“…In our study, this oil demonstrated only poor antibacterial and antifungal activity (Table S1). On the contrary, low percentages of borneol and α-pinene in Ampelopsis megalophylla as reported by Xie et al (2014) and caryophyllene (Joycharat et al 2014) show high microbiological activity. TTO which exhibited MIC values of 3.12 mg/ml.…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 65%
“…The phytochemical constituents of several other species of Aglaia have been reported earlier [8][9][10][11]. Most researches on the bioactivities of various species of Aglaia, like molluscidal, anti-inflammatory, insecticidal and antimicrobial activities have been supported with their chemical constituents [12][13][14] and this reveals the importance of the phytochemicals of this particular genus in therapeutics.…”
Section: Discussionmentioning
confidence: 83%
“…The flowers of A. odorata are used to perfume clothes (Janprasert et al 1992). The extracts from A. odorata has antimicrobial properties (Joycharat et al 2014). It has been used as a traditional herb to treat heart disease, bruises, traumatic injury, and pyresis (Kato-Noguchi et al 2016).…”
Section: Aglaia Odorata; Chloroplast; Illumina Sequencing; Phylogenetmentioning
confidence: 99%